2000
DOI: 10.1016/s0197-4580(00)00133-0
|View full text |Cite
|
Sign up to set email alerts
|

The relation between global and limbic brain volumes on MRI and cognitive performance in healthy individuals across the age range

Abstract: The present study investigated the range of age-related changes in brain morphology and the relation with performance on memory and other cognitive tests in a healthy population. A group of 61 subjects (21 to 81 years old, mean ϭ 55.7), free from cognitive and medical deficits, underwent MRI scanning and neuropsychological assessment encompassing memory and other cognitive tests. Volumetry of the hippocampus, parahippocampal gyrus, mamillary bodies, third ventricle, and total brain matter was performed. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
79
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 38 publications
(64 reference statements)
13
79
2
1
Order By: Relevance
“…This is in contrast to a substantial number of MRI studies reporting a reliable age-related decline in hippocampal volume in healthy humans (Kaye et al 1997;Mueller et al 1998;Tisserand et al 2000;Raz et al 2004;Walhovd et al 2009). While total hippocampal volume is unaltered with age in rhesus monkeys, it correlates with DR acquisition and average accuracy (Shamy et al 2010), consistent with literature suggesting that the hippocampus modulates working memory (Friedman and Goldman-Rakic 1988;Eberling et al 1997).…”
Section: Gross Anatomy Of Hippocampal and Related Cortical Regionscontrasting
confidence: 81%
“…This is in contrast to a substantial number of MRI studies reporting a reliable age-related decline in hippocampal volume in healthy humans (Kaye et al 1997;Mueller et al 1998;Tisserand et al 2000;Raz et al 2004;Walhovd et al 2009). While total hippocampal volume is unaltered with age in rhesus monkeys, it correlates with DR acquisition and average accuracy (Shamy et al 2010), consistent with literature suggesting that the hippocampus modulates working memory (Friedman and Goldman-Rakic 1988;Eberling et al 1997).…”
Section: Gross Anatomy Of Hippocampal and Related Cortical Regionscontrasting
confidence: 81%
“…Indeed, after adjusting for intracranial volume and total brain size, the volume of the thalamus correlates significantly with the performance on a variety of tasks in the domains of speeded processing and working memory. After additionally partialling out the previous studies that could not find such a relation with cognitive speed for other structures in the brain, using thalamic activation in elderly subjects in paradigms of similar methodologies [48].…”
Section: Discussionmentioning
confidence: 99%
“…This was done since previconfounding variable. It has been shown that age explains ous research has shown that elderly subjects considered the major part of the variance in cognitive performance in 'gerontologically healthy' might be structurally or cognistudies that use a wide age-range [48]. tively affected by conditions such as diabetes mellitus, Of one subject in the young group, no neuropsychologimild hypertension or repeated anaesthesia [17, 41,16,50].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into the consideration the importance of the MTL in memory processing, a large number of cross-sectional volumetric neuroimaging studies were performed. They predominantly focused on the comparison of MTL structure volumes, or the degree of their atrophy, between healthy individuals, age-matched cases suffering from mild cognitive impairment (MCI) and cases at different stages of Alzheimer's disease (AD) [5][6][7][8][9][10][11][12][13][14][15]. Their results showed a significant reduction of MTL component volumes in cases with mild cognitive impairment and AD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings, and the fact that in the early phases of AD the first pathological changes occur in the entorhinal cortex [5][6][7][8][9][10][11][12][13][14][15], stressed the importance of the histological findings, especially of MTL areas, that might improve the understanding of the cellular basis for the various degrees of cognitive decline within healthy elderly populations. Until recently it was generally believed that age-related impairments in cognitive performance are the result of age-related neuron loss, especially within the hippocampus and most neocortical areas.…”
Section: Introductionmentioning
confidence: 99%